2012
DOI: 10.1091/mbc.e12-04-0276
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin-7a reverses the ERF-induced inhibition of EMT in Ras-dependent mouse mammary epithelial cells

Abstract: EMT requires cooperation of the EGF/Ras with the TGF-β signaling pathways in a multistep process. ERF, a bona fide Ras-Erk effector, inhibits TGF-β–induced EMT via Semaphorin-7a repression, and Semaphorin-7a induction is required for EMT progress. These data provide new insights into the Ras–TGF-β interconnection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 57 publications
3
55
0
2
Order By: Relevance
“…Quantitative RT-PCR confirmed that DLG5 was most highly expressed in placental tissue (Figure 2C) and was localized to the syncytium (Figure 2D). Similarly, semaphoring-7a, ( SEMA7A ) has also been implicated in regulating TGF-β induced EMT [23]. SEMA7A is a signaling molecule that is transcriptionally regulated by Ets2-receptor factor and HIF-1α and has been involved in the regulation of cell migration in the immune and nervous systems, as well as in cancer (recently reviewed, [24]).…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative RT-PCR confirmed that DLG5 was most highly expressed in placental tissue (Figure 2C) and was localized to the syncytium (Figure 2D). Similarly, semaphoring-7a, ( SEMA7A ) has also been implicated in regulating TGF-β induced EMT [23]. SEMA7A is a signaling molecule that is transcriptionally regulated by Ets2-receptor factor and HIF-1α and has been involved in the regulation of cell migration in the immune and nervous systems, as well as in cancer (recently reviewed, [24]).…”
Section: Resultsmentioning
confidence: 99%
“…262 Likewise, it was reported to contribute to the metastasis of breast cancer cells by promoting epithelial to mesenchymal transition. 263 Recently, sema7A was found to be upregulated in oral squamous cell carcinoma, to promote their proliferation of these tumor cells, and to enhance their invasiveness. 264 …”
mentioning
confidence: 99%
“…Likewise, ERK activation by mechanical force was found to be essential for the induction of a myofibroblast phenotype [46]. Conversely, a study by Allegra et al ., has shown that epithelial-to-mesenchymal transition was inhibited by the activation of the Ras/ERK pathway due at least partially to the regulation of semaphorin-7A expression [47]. This demonstrates a close association between semaphorin-7A and the MAPK pathway.…”
Section: Discussionmentioning
confidence: 79%